Evaluation of In-vitro Antioxidant and Antibacterial Properties of Commelina nudiflora L. Extracts Prepared by Different Polar Solvents - Palaniselvam, Kuppusamy; M. M., Yusoff; Narasimha, Reddy Parine; Natanamurugaraj, Govindan (Elsevier B.V., 2015)
The study explored on the commonly available weed plant Commelina nudiflora which has potential in-vitro antioxidant and antimicrobial activity. The different polar solvents such as ethanol, chloroform, dichloromethane, hexane and aqueous were used for the soxhlet extraction. The extracts were identified pharmacologically as important bioactive compounds and their potential free radical scavenging activities, and antimicrobial properties were studied. C. nudiflora extracts were monitored on their in-vitro antioxidant ability by DPPH and ABTS radical scavenging assay. Aqueous extract shows significant free radical scavenging activity of 63.4 mg/GAE and 49.10 mg/g in DPPH and ABTS respectively. Furthermore, the aqueous crude extract was used in antibacterial studies, which shows the highest inhibitory activity against Pseudomonas aeruginosa, Escherichia coli and Salmonella typhi. Among all the extracts, aqueous extract of C. nudiflora has significant control over free radical scavenging activity and inhibition of the growth of food pathogenic bacteria. Also, the aqueous extract contains abundance of phenolics and flavonoids higher than other extracts. This study explored weed plant C. nudiflora as a potential source of antioxidant and antibacterial efficacy and identified various therapeutic value bioactive compounds from GC–MS analysis.